Cooperative loss electromagnetic wave composite film with micro-nano interlocking structure and preparation method thereof

By combining CNTs with MXene to form a composite film with micro-nano interlocking structure, the limitations of MXene materials in wave absorption performance are solved, and efficient electromagnetic wave absorption and loss is achieved, which is suitable for stealth technology in military and electronic equipment.

CN119133876APending Publication Date: 2024-12-13LOGISTICAL ENGINEERING UNIVERSITY OF PLA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411262912.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Due to the low permeability and single loss mechanism, MXene materials have limitations in their absorbing performance and practical applications, especially their impedance does not match the free space, resulting in high reflectivity and low absorbing performance.

Method used

By combining the dielectric material CNTs with the conductive material MXene, a micro-nano interlocking porous structure film is formed, and the one-dimensional linear structure of CNTs and the two-dimensional sheet structure of MXene is used to form a composite material to enhance its dielectric loss performance. The suspension prepared by acid etching and ultrasonic dispersion technology achieves uniform dispersion and vacuum suction filtration to form a micro-nano interlocking structure.

Benefits of technology

It significantly improves the electromagnetic wave absorption performance of composite materials, realizes the dual mechanism of conductivity loss and dielectric loss, improves wave absorption performance, and reduces production costs and energy consumption, and is suitable for stealth technology for military and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133876A_ABST
    Figure CN119133876A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional materials, in particular to a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure and a preparation method, the composite film comprises a dielectric material CNTs and a conductive material MXene, the CNTs are a nanoscale one-dimensional linear material, and the MXene is a micron-scale two-dimensional sheet material. The preparation method comprises the steps that CNTs powder is provided, an MXene suspension liquid is prepared through an acid etching method, and MXene in the suspension liquid is in a micron order; adding CNTs powder into the MXene suspension, stirring, and carrying out ultrasonic dispersion to obtain a dispersion liquid; and carrying out vacuum filtration on the dispersion liquid to obtain the collaborative loss electromagnetic wave composite film with the micro-nano interlocking structure in the claim 1 or 2. The MXene two-dimensional transition metal material has a double loss mechanism of conductivity loss and dielectric loss, is more effective for loss of electromagnetic waves, and can solve the problem that the MXene two-dimensional transition metal material is difficult to achieve higher electromagnetic wave absorptivity due to a single loss mechanism and high reflectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure and a preparation method thereof. Background Art

[0002] At present, with the rapid development of wireless communications and electronic equipment, a large amount of electromagnetic interference and electromagnetic pollution will inevitably occur, and even pose a potential threat to the human immune system and central nervous system. And with the continuous development of anti-radar stealth technology, the survivability of various military weapons and military bases in combat has been greatly reduced. Absorbing materials can absorb and consume electromagnetic waves and convert them into other energy, effectively reducing the probability of military systems being detected by radar. Therefore, the design and application of electromagnetic wave absorbing materials has become one of the important research directions in the military field.

[0003] MXene is a new type of two-dimensional transition metal carbide with many excellent physical and chemical properties such as rich surface functional groups, high intrinsic conductivity, and tunable dielectric properties. It has good application prospects in the fields of sensing, electromagnetic absorption, and supercapacitors. However, due to the low magnetic permeability of MXene, its impedance does not match the free space, resulting in only a single loss mechanism. In addition, MXene mainly reflects rather than absorbs and loses electromagnetic waves, which limits its absorption performance and practical application. In order to improve the absorption performance of MXene, it is urgent to develop composite materials based on MXene.

[0004] In order to improve the low porosity, poor impedance matching performance, and low wave absorption performance caused by electrical loss of the thin film composed of a single sheet structure of MXene, the present invention adopts an effective method to add the dielectric material CNTs to MXene. Then, the one-dimensional linear structure of CNTs can form a micro-nano interlocked porous structure film with the two-dimensional sheet structure of MXene. The addition of dielectric materials helps to improve the dielectric loss performance of the composite material. The composite film is a three-dimensional porous structure, and electromagnetic waves can be reflected and lost multiple times in many holes, so it can form an electromagnetic wave synergistic loss composite material with a micro-nano interlocked porous structure. Summary of the invention

[0005] The purpose of the present invention is to provide a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure and a preparation method, which can solve the problem of difficulty in achieving a higher electromagnetic wave absorption rate due to the single loss mechanism and high reflectivity of MXene two-dimensional transition metal materials.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure, comprising a dielectric material CNTs and a conductive material MXene, wherein the CNTs are nanoscale one-dimensional linear materials, and the MXene is a micron-scale two-dimensional sheet material.

[0007] Furthermore, the weight ratio of the dielectric material CNTs to the conductive material MXene is 1-5:5-9.

[0008] In a second aspect, the present invention provides a method for preparing a cooperative loss electromagnetic wave composite film having a micro-nano interlocking structure, characterized in that it comprises: Providing CNTs powder, and preparing a MXene suspension by an acid etching method, wherein the MXene in the suspension is in micrometer size; Add CNTs powder into MXene suspension, stir, and ultrasonically disperse to obtain a dispersion; The dispersion is vacuum filtered to obtain the above-mentioned cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure.

[0009] Furthermore, the solid matter in the dispersion includes 50-90% of MXene and 10-50% of CNTs powder by mass.

[0010] Furthermore, the process of preparing MXene suspension by acid etching is as follows: Using MAX phase as raw material and hydrofluoric acid solution as etching solution, the A atomic layer in the MAX phase is selectively etched to obtain an intermediate product; the chemical formula of the MAX phase is M n+1 AX n , M is Ti, V or Nb, A is Al, Sn, Ge or Sb, and X is C or N; The intermediate product is added to a lithium fluoride intercalation solution and exfoliated to obtain a MXene dispersion; The MXene dispersion is stirred and centrifuged to obtain a precipitate, which is then dispersed in deionized water, suspended, and centrifuged to obtain an upper suspension, which is the MXene suspension.

[0011] Further, the etching solution also includes a hydrochloric acid solution; The etching solution comprises, by volume, 2 parts by volume of a hydrofluoric acid solution, 12 parts by volume of a hydrochloric acid solution and 6 parts by volume of water; During etching, the concentration of the MAX phase in the etching solution is 0.03-0.05 g / mL.

[0012] Furthermore, the concentration of the hydrochloric acid solution is 20-36 wt.%, and the concentration of the hydrofluoric acid solution is 36-49 wt.%.

[0013] The present invention has the following unexpected beneficial effects: 1. The present invention adds dielectric material CNTs to MXene, and forms a micro-nano interlocked porous structure film through one-dimensional linear CNTs and two-dimensional sheet MXene. The addition of dielectric material helps to improve the dielectric loss performance of the composite material, so that the film has a dual loss mechanism of conductivity loss and dielectric loss, which is more effective for the loss of electromagnetic waves. Moreover, the obtained composite film is a three-dimensional porous structure, which can make it easier for electromagnetic waves to enter the material. Electromagnetic waves can be reflected and lost multiple times in many holes, further absorbing and losing electromagnetic waves, and improving the wave absorption performance.

[0014] 2. The synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure described in the present invention improves the low porosity, poor impedance matching performance and low wave absorption performance caused by electrical loss of the film composed of a single sheet structure of MXene, and solves the problem of difficulty in achieving a high electromagnetic wave absorption rate due to the single loss mechanism and high reflectivity of MXene two-dimensional transition metal materials.

[0015] 3. The preparation method of the present invention is simple to operate, low in cost, and can realize actual production in large quantities with low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a SEM image of the multilayer MXene prepared in Example 1 of the present invention; Figure 2 is a SEM image of a single-layer MXene prepared in Example 1 of the present invention; Figure 3 is the XRD pattern of the single-layer MXene prepared in Example 1 of the present invention; Figure 4 This is a SEM image of the cross section of the cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0018] In one embodiment, the present invention provides a cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure, including a dielectric material CNTs and a conductive material MXene, wherein the CNTs are nanoscale one-dimensional linear materials, and the MXene is a micron-scale two-dimensional sheet material.

[0019] The present invention adds dielectric material CNTs to MXene, and forms a micro-nano interlocked porous structure film through one-dimensional linear CNTs and two-dimensional sheet MXene. The addition of dielectric material helps to improve the dielectric loss performance of the composite material, so that the film has a dual loss mechanism of conductivity loss and dielectric loss, which is more effective for the loss of electromagnetic waves. In addition, the obtained composite film is a three-dimensional porous structure, which can make it easier for electromagnetic waves to enter the interior of the material. Electromagnetic waves can be reflected and lost multiple times in many holes, further absorbing and losing electromagnetic waves, and improving the wave absorption performance.

[0020] CNTs or carbon nanotubes have excellent electrical conductivity, mechanical strength and thermal stability. Their nanoscale size gives them unique advantages in the field of electromagnetic wave absorption. The one-dimensional linear structure of CNTs is conducive to the formation of a conductive network, promoting the rapid transmission of electrons, thereby enhancing the response to electromagnetic waves. In composite films, CNTs act as conductive channels that can effectively guide current and increase the scattering and absorption of electromagnetic waves.

[0021] MXene is obtained by etching transition metal carbides or nitrides, and has excellent conductivity, hydrophilicity and high specific surface area. Its micron-scale flaky structure provides rich interfaces and interlayer interactions for composite films.

[0022] MXene not only enhances the conductivity of composite materials as a conductive component, but also provides a large number of interface scattering points through its unique two-dimensional structure, further increasing the reflection and scattering of electromagnetic waves inside the material, thereby improving the electromagnetic wave loss efficiency.

[0023] During the composite process, CNTs and MXene are intertwined and nested through physical methods to form a micro-nano interlocking structure. This structure not only enhances the mechanical strength of the material, but also optimizes the transmission path of electromagnetic waves inside the material. The micro-nano interlocking between CNTs and MXene promotes the rapid transmission of electrons between the two, forming a more complex conductive network. At the same time, this structure increases the number of reflections, scatterings and absorptions of electromagnetic waves inside the material, significantly improving the electromagnetic wave loss efficiency.

[0024] The synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure described in the present invention improves the low porosity, poor impedance matching performance and low wave absorption performance caused by electrical loss of the film composed of a single sheet structure of MXene, and solves the problem of difficulty in achieving a high electromagnetic wave absorption rate due to the single loss mechanism and high reflectivity of MXene two-dimensional transition metal materials.

[0025] The composite film has broad application prospects in the fields of electromagnetic wave absorption, electromagnetic shielding, stealth technology, etc. For example, in the fields of electronic equipment, communication equipment, aerospace, etc., it can effectively reduce the impact of electromagnetic radiation on the environment and human body; in the military field, it can be used to improve the stealth performance of military equipment and reduce the risk of detection.

[0026] In a preferred embodiment, the weight ratio of the dielectric material CNTs and the conductive material MXene is 1~5:5~9. On the one hand, the appropriate ratio of CNTs to MXene can balance the conductivity and electromagnetic wave scattering effect, so that the composite film can maintain a high electromagnetic wave loss capacity in a wide frequency range. On the other hand, the two-dimensional sheet structure of MXene helps to enhance the mechanical strength of the composite film, and the addition of CNTs further improves the toughness and tensile resistance of the composite film. By limiting the ratio of CNTs to MXene, the mechanical properties of the composite film can be balanced.

[0027] In one embodiment, the present invention provides a method for preparing a cooperative loss electromagnetic wave composite film having a micro-nano interlocking structure, characterized in that it includes: Providing CNTs powder, and preparing a MXene suspension by an acid etching method, wherein the MXene in the suspension is in micrometer size; Add CNTs powder into MXene suspension, stir, and disperse by ultrasonic to obtain dispersion; The dispersion is vacuum filtered to obtain the above-mentioned cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure.

[0028] The detailed steps of the preparation method are described below.

[0029] 1. Provide CNTs powder. First, high-quality CNTs (carbon nanotubes) powder needs to be prepared as a dielectric material. CNTs powder should have good conductivity and dispersibility to ensure that it can be evenly dispersed in the MXene suspension in the subsequent steps.

[0030] 2. Prepare MXene suspension by acid etching. MXene is usually prepared by selectively etching A element (such as Al) from MAX phase (such as Ti3AlC2). Acid etching is a commonly used preparation method that uses strong acid (such as hydrofluoric acid) to react with MAX phase to remove the A element layer, leaving a two-dimensional sheet structure composed of transition metal carbides or nitrides, namely MXene.

[0031] The MXene flakes in the prepared MXene suspension are micrometer-sized and have good dispersibility and conductivity. These micrometer-sized MXene flakes will provide rich interfaces and interlayer interactions for the composite film.

[0032] 3. Add CNTs powder to MXene suspension. Slowly add the prepared CNTs powder to the MXene suspension while stirring to ensure that the CNTs can be evenly dispersed in the MXene suspension. Through this step, CNTs and MXene begin to contact each other, laying the foundation for the subsequent formation of micro-nano interlocking structure.

[0033] 4. Ultrasonic dispersion. On the basis of stirring, the mixed liquid is subjected to ultrasonic treatment. Ultrasonic dispersion can further break up the agglomerates of CNTs and MXene, promote their uniform dispersion in the suspension, improve the dispersibility of CNTs and MXene, and ensure their uniform distribution in the composite film.

[0034] 5. Vacuum filter the dispersion. The ultrasonically dispersed mixed solution is vacuum filtered. During the filtration process, CNTs and MXene gradually accumulate on the filter membrane to form a thin film. Due to the interaction between CNTs and MXene and the physical extrusion during the filtration process, a micro-nano interlocking structure is formed between them.

[0035] Through vacuum filtration, CNTs and MXene are separated from the suspension, and a composite film with a micro-nano interlocking structure is formed on the filter membrane. This structure can significantly improve the electromagnetic wave loss capacity of the composite film.

[0036] The preparation method of the present invention is simple to operate, low in cost, and can realize practical production in large quantities with low energy consumption.

[0037] In a preferred embodiment, the solid matter in the dispersion includes 50-90% MXene and 10-50% CNTs powder by mass.

[0038] As a conductive material, a high content of MXene helps to improve the conductivity and electromagnetic wave loss capacity of the composite film. As the MXene content increases, the conductive network in the composite film will become denser, and the electron transmission efficiency will be improved, thereby enhancing the response to electromagnetic waves. However, too high a MXene content may also lead to a decrease in the mechanical properties of the composite film, such as reduced toughness and fragility. Therefore, it is necessary to find a balance between conductivity and mechanical properties.

[0039] As a dielectric material, the appropriate addition of CNTs can improve the dielectric properties of the composite film and form a micro-nano interlocking structure with MXene, further enhancing the electromagnetic wave loss capacity. The one-dimensional linear structure of CNTs helps to form a conductive channel in the composite film and promote the rapid transmission of electrons. At the same time, its high specific surface area also provides more scattering and absorption points for electromagnetic waves. Too low a CNTs content may not fully exert its dielectric properties and conductive channel function; while too high a content may cause the conductive network to be too dense, affecting the transmission path of electromagnetic waves inside the material.

[0040] By adjusting the mass fraction of MXene and CNTs powders, the performance of the composite film can be precisely controlled. For example, in situations where higher electromagnetic wave loss capacity is required, the MXene content can be appropriately increased; in situations where better mechanical properties are required, the MXene content can be appropriately reduced and the CNTs content can be increased.

[0041] In addition, the performance of the composite film can be further optimized by changing the type, size and other parameters of MXene and CNTs according to the needs of specific application scenarios.

[0042] In a preferred embodiment, the process of preparing MXene suspension by acid etching is as follows: Using the MAX phase as the raw material and the hydrofluoric acid solution as the etching solution, hydrofluoric acid (HF) can selectively react with the A atomic layer in the MAX phase, thereby removing the A layer and leaving a multi-layered structure composed of transition metal carbides or nitrides, i.e., the intermediate product.

[0043] The chemical formula of the MAX phase is M n+1 AX n , M is Ti, V or Nb, A is Al, Sn, Ge or Sb, and X is C or N; The intermediate product is added to the lithium fluoride intercalation solution and stripped to obtain a MXene dispersion. The role of the lithium fluoride intercalation solution is to insert lithium ions between MXene layers, thereby expanding the interlayer spacing, reducing the interlayer interaction force, and making the MXene layer easier to strip. Through stirring or ultrasonic treatment and other methods, lithium fluoride and the intermediate product are fully reacted to achieve MXene stripping. The stripped MXene exists in the form of a dispersion, which contains a large number of MXene sheets.

[0044] The MXene dispersion is stirred and centrifuged to obtain a precipitate. Stirring helps to further disperse and homogenize the MXene flakes, while centrifugation can precipitate large particles or impurities that are not completely peeled off.

[0045] The upper suspension after centrifugation is the initially purified MXene suspension. However, in order to obtain a higher purity MXene suspension, multiple stirring, centrifugation and deionized water suspension processes are usually required. Through this step, impurities and incompletely peeled MXene sheet fragments in the suspension can be further removed.

[0046] After multiple purifications, the MXene suspension obtained has high purity and good dispersibility. At this time, the MXene flakes are evenly dispersed in the suspension at the micron level, providing high-quality raw materials for the subsequent preparation of composite films.

[0047] In a preferred embodiment, the etching solution further includes a hydrochloric acid solution; in parts by volume, the etching solution includes 2 parts by volume of a hydrofluoric acid solution, 12 parts by volume of a hydrochloric acid solution and 6 parts by volume of water.

[0048] Hydrofluoric acid solution: As the main etchant, hydrofluoric acid (HF) is responsible for selectively etching the A atomic layer in the MAX phase. In this preferred embodiment, the concentration of the hydrofluoric acid solution is 49 wt.%, that is, the mass fraction is 49%, which means that 49 grams of hydrofluoric acid are contained in every 100 grams of solution.

[0049] Hydrochloric acid solution: The addition of hydrochloric acid (HCl) can assist hydrofluoric acid in etching, shorten the reaction time, and improve etching efficiency and uniformity. Preferably, the concentration of the hydrochloric acid solution is 36 wt.%, that is, 36 grams of hydrochloric acid are contained in every 100 grams of solution.

[0050] Water: As a solvent, water is used to dilute hydrofluoric acid and hydrochloric acid and adjust the concentration and reaction rate of the etching solution.

[0051] During etching, the concentration of MAX phase in the etching solution is 0.05 g / mL, that is, each milliliter of etching solution contains 0.05 grams of MAX phase raw material. This concentration is selected to ensure that the etching reaction can proceed fully, while avoiding uneven reaction or waste of raw materials caused by excessive concentration of raw materials.

[0052] The etching reaction is usually carried out at room temperature, but the temperature can be adjusted as needed. Stirring is necessary to ensure that the etching solution is fully in contact with the MAX phase and reacts evenly. The reaction time depends on factors such as the type of MAX phase, the concentration of the etching solution and the temperature, and the optimal conditions need to be determined through experiments.

[0053] The present invention can obtain MXene sheets with higher purity and better dispersion by optimizing the etching solution composition and reaction conditions. In addition, reasonable etching solution ratio and raw material concentration are helpful to reduce production costs and improve economic benefits.

[0054] The following is an analysis and explanation in conjunction with specific embodiments.

[0055] Embodiment 1, a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure, comprising a dielectric material CNTs and a conductive material MXene, wherein the CNTs are nano-scale one-dimensional linear materials, and the MXene is a micron-scale two-dimensional sheet material. The weight ratio of the dielectric material CNTs to the conductive material MXene is 1:1.

[0056] The method for preparing the cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure comprises the following steps: Step 1: add 1 g of Ti3AlC2 into 20 mL of etching solution, which contains 2 mL of 49 wt.% HF, 12 mL of 36 wt.% HCl and 6 mL of deionized water, and stir at room temperature and 250 rpm for 24 hours to obtain Ti3C2; Step 2: The Ti3C2 obtained in step 1 is repeatedly centrifuged with deionized water at a speed of 3500 rpm for 5 minutes each time until the pH value of the supernatant is greater than 6, thereby obtaining a multilayered Ti3C2.

[0057] The obtained product was subjected to XRD analysis. Figure 1 As shown, this is the XRD pattern of the Ti3C2 film, with 2θ=5.8°, 18°, and 30° being the (002), (006), and (010) peaks, respectively.

[0058] The observed microstructure of the multilayered Ti3C2 is shown in Figure 2 As shown, its morphology is accordion-shaped, and the interlayer spacing is increased by removing Al in MAX through acid etching.

[0059] Then, the obtained multilayered Ti3C2 was added into the lithium chloride intercalation solution and stirred at a rotation speed of 500 rpm for 4 hours.

[0060] Finally, the stirred suspension was centrifuged at a rotation speed of 3500 rpm for 30 minutes, and the obtained precipitate was washed 4 times with deionized water to obtain a single-layer Ti3C2.

[0061] The microstructure of the observed single-layer Ti3C2 is shown in Figure 3 As shown, the single-layer Ti3C2 crystal structure is complete, with no obvious defects on the surface and a size of about 10~13 μm.

[0062] Step three, disperse the precipitate obtained in step two in deionized water, suspend for 5 minutes, centrifuge at a speed of 3500 rpm for 5 minutes, take the upper dark green viscous suspension, which is the uniformly distributed single-layer Ti3C2 suspension, and determine the concentration of the single-layer Ti3C2 suspension by filtering a certain amount of solution to obtain the mass of the film layer after drying.

[0063] Step 4: According to the ratio, add CNTs powder to the MXene suspension, stir magnetically for 2 hours, and then continue ultrasonication for 1 hour to obtain a MXene / CNTs dispersion.

[0064] Step 5: Add the dispersion into a suction filtration bottle and perform vacuum filtration to obtain a MXene / CNTs composite wet film.

[0065] Step 6: The MXene / CNTs composite wet film obtained by vacuum filtration is vacuum dried at a temperature of 105°C for 6 hours to form a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure.

[0066] Observe the cross-sectional microstructure of the prepared synergistic lossy electromagnetic wave composite film with micro-nano interlocking structure. The results are shown in Figure 4 As shown, the linear CNTs are evenly distributed in the flaky MXene nanosheets, making the membrane layer porous.

[0067] Embodiment 2, a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure, comprising a dielectric material CNTs and a conductive material MXene, wherein the CNTs are nano-scale one-dimensional linear materials, and the MXene is a micron-scale two-dimensional sheet material. The weight ratio of the dielectric material CNTs to the conductive material MXene is 1:9. The preparation method of the synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure is the same as that of Embodiment 1.

[0068] Embodiment 3, a synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure, comprising a dielectric material CNTs and a conductive material MXene, wherein the CNTs are nano-scale one-dimensional linear materials, and the MXene is a micron-scale two-dimensional sheet material. The weight ratio of the dielectric material CNTs to the conductive material MXene is 3:7.

[0069] The method for preparing the cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure is the same as that in Example 1.

[0070] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A synergistic loss electromagnetic wave composite film with a micro-nano interlocking structure, characterized in that: It includes dielectric material CNTs and conductive material MXene, wherein the CNTs are nanometer-scale one-dimensional linear materials, and the MXene is micrometer-scale two-dimensional sheet material.

2. The synergistic lossy electromagnetic wave composite film with a micro-nano interlocking structure according to claim 1, characterized in that: The weight ratio of the dielectric material CNTs to the conductive material MXene is 1-5:5-9.

3. A method for preparing a cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure, characterized in that: include: Providing CNTs powder, and preparing a MXene suspension by an acid etching method, wherein the MXene in the suspension is in micrometer size; Add CNTs powder into MXene suspension, stir, and ultrasonically disperse to obtain a dispersion; The dispersion is vacuum filtered to obtain the cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure as claimed in claim 1 or 2.

4. The method for preparing a cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure according to claim 3, characterized in that: By mass fraction, the solid matter in the dispersion includes 50-90% MXene and 10-50% CNTs powder.

5. The method for preparing a lossy electromagnetic wave composite film having a micro-nano interlocking structure according to claim 3, characterized in that: The process of preparing MXene suspension by acid etching is as follows: Using MAX phase as raw material and hydrofluoric acid solution as etching solution, the A atomic layer in the MAX phase is selectively etched to obtain an intermediate product; the chemical formula of the MAX phase is M n+1 AX n , M is Ti, V or Nb, A is Al, Sn, Ge or Sb, and X is C or N; The intermediate product is added to a lithium fluoride intercalation solution and exfoliated to obtain a MXene dispersion; The MXene dispersion is stirred and centrifuged to obtain a precipitate, which is then dispersed in deionized water, suspended, and centrifuged to obtain an upper suspension, which is the MXene suspension.

6. The method for preparing a cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure according to claim 5, characterized in that: The etching solution also includes a hydrochloric acid solution; The etching solution comprises, by volume, 2 parts by volume of a hydrofluoric acid solution, 12 parts by volume of a hydrochloric acid solution and 6 parts by volume of water; During etching, the concentration of MAX phase in the etching solution is 0.03~0.05g / mL.

7. The method for preparing a cooperative loss electromagnetic wave composite film with a micro-nano interlocking structure according to claim 6, characterized in that: The concentration of the hydrochloric acid solution is 20-36 wt.%, and the concentration of the hydrofluoric acid solution is 36-49 wt.%.

Citation Information

Cited By

  • Two-dimensional MBene-metal sulfide composite material as well as preparation method and application thereof

    CN120049205A